The Impact of the COVID-19 Pandemic and Lockdown on Mild Cognitive Impairment, Alzheimer's Disease and Dementia With Lewy Bodies in China: A 1-Year Follow-Up Study - Chen, Zhi-Chao; Liu, Shuai; Gan, Jinghuan; Ma, Lingyun; Du, Xiaoshan; Zhu, Han; Han, Jiuyan; Xu, Junying; Wu, Hao; Fei, Min; Dou, Yuchao; Yang, Yaqi; et al. (Frontiers in Psychiatry, 2021)
Background While the lockdown strategies taken by many countries effectively limited the spread of COVID-19, those were thought to have a negative impact on older people. This study aimed to investigate the impact of lockdown on cognitive function and neuropsychiatric symptoms over a one-year follow-up period in patients with mild cognitive impairment (MCI), Alzheimer's disease (AD) and dementia with Lewy bodies (DLB). Methods We enrolled consecutive patients with MCI, probable AD or DLB who were receiving outpatient memory care before the COVID-19 pandemic and followed-up with them after one year by face-to-face during the COVID-19 pandemic to assess changes in physical activity, social contact, cognitive function and neuropsychiatric symptoms (NPS). Results Total 105 probable AD, 50 MCI and 22 probable DLB patients were included and completed the one-year follow-up between 31 October and 30 November 2020. Among the respondents, 42% of MCI, 54.3% of AD and 72.7% of DLB patients had a decline in MMSE scores and 54.4% of DLB patients had worsening Neuropsychiatric inventory (NPI) scores. Patients with DLB showed a more rapid decline of MMSE than those with AD. Diminished physical activity and social contact might have hastened the deterioration of cognition and the worsening of NPS. Conclusion Social isolation and physical inactivity even after strict lockdown for at least 6 months were correlated with accelerated decline of cognitive function and NPS in patients with AD and DLB.